2009
DOI: 10.1038/oby.2008.565
|View full text |Cite
|
Sign up to set email alerts
|

Are Natural Killer Cells Protecting the Metabolically Healthy Obese Patient?

Abstract: With the emerging obesity pandemic, identifying those who appear to be protected from adverse consequences such as type 2 diabetes and certain malignancies will become important. We propose that the circulating immune system plays a role in the development of these comorbidities. Clinical data and blood samples were collected from 52 patients with severe obesity attending a hospital weight‐management clinic and 11 lean healthy controls. Patients were classified into metabolically “healthy obese” (n = 26; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
173
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(205 citation statements)
references
References 26 publications
14
173
0
13
Order By: Relevance
“…Determination of the prevalence of metabolically healthy obese individuals The diagnosis of MHO was obtained based on a BMIX30 kg/m 2 and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;AguilarSalinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009), as described in a previous paper (Velho et al, 2010). As one definition of MHO includes CRP levels (Wildman et al, 2008), analysis of CRP levels was not performed for this definition.…”
Section: Biological Datamentioning
confidence: 99%
“…Determination of the prevalence of metabolically healthy obese individuals The diagnosis of MHO was obtained based on a BMIX30 kg/m 2 and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;AguilarSalinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009), as described in a previous paper (Velho et al, 2010). As one definition of MHO includes CRP levels (Wildman et al, 2008), analysis of CRP levels was not performed for this definition.…”
Section: Biological Datamentioning
confidence: 99%
“…The diagnosis of MHO was obtained based on the joint combination of each obesity marker (BMI, waist circumference and body fat percentage) and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;Aguilar-Salinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009) (Table 1). There were no exclusion criteria such as menopause, hormonal use and medications affecting metabolism, as well as diabetes and CVDs; participants were selected if they presented with overweight or obesity using the different anthropometric markers (BMI, waist or body fat).…”
Section: Determination Of the Prevalence Of Metabolically Healthy Obesementioning
confidence: 99%
“…There are currently no unique criteria for MHO, and several definitions have been proposed (Meigs et al, 2006;Aguilar-Salinas et al, 2008;Karelis, 2008;Wildman et al, 2008;Lynch et al, 2009). The criteria used to define MHO are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…However as of yet, their role has not been fully elucidated in the chronic inflammation that is characteristic of obesity. Lynch et al have reported significant reductions of circulating NK cells in metabolically unhealthy obese subjects, suggesting that a lack of NK cells in the periphery is detrimental for metabolic health (83) . Lynch et al also reported significant expansions of circulating inhibitory-receptor bearing and CD69 + NK cells in metabolically unhealthy obese individuals, compared with healthy controls, suggesting that peripheral NK cells in metabolically unhealthy obese patients were activated but unable to elicit effector functions, making such individuals more susceptible to disease (83) .…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…CD8 + T Cytotoxicity -directly kill abnormal cells Promote inflammation (80) , macrophage recruitment (81,82) NK Cytotoxicity -kill abnormal cells Decreased in blood, impaired function (83) (89,90) iNKT, invariant natural killer T cells; MAIT, mucosal associated invariant T cells; NK, natural killer; VAT, visceral adipose tissue.…”
Section: M2mentioning
confidence: 99%